Evaluation of the effect of glycerol supplementation on the anaerobic digestion of real municipal solid waste in batch mode. (1st April 2017) - Zahedi, S.; Solera, R.; García-Morales, J.L.; Ennouri, H.; Sales, D.
Abstract: The effect of low glycerol supplementation (<1% v/v) in the thermophilic anaerobic digestion (AD) of real municipal solid waste (RMSW) on methane production (MP) is not known. This study explores the effect of five different glycerol supplementations (0%, 0.1%, 0.25%, 0.5% and 1%) on effluent characteristics, anaerobic consortia and MP. Specifically, by adding 0.25% v/v crude glycerol to the feed, the methane production rate increased by 48% (from 7.40 ± 1.17 l CH4 /l to 11.01 ± 1.66 l CH4 /l), in line with the increase in total volatile solids (TVS) removal (from 65 ± 7% to 81 ± 7) and methanogenic activity (from 110 ∗ 10 −12 ± 17 ∗ 10 −12 l CH4 /cell to 156 ∗ 10 −12 ± 24 ∗ 10 −12 l CH4 /cell). Extra glycerol added to the feed (0.5% or 1%) was shown to be non-feasible for thermophilic AD of RMSW, as inhibition of methanogenesis was observed. Fluorescent in situ hybridization (FISH) studies showed that the percentages of Eubacteria, Archaea, H2 -utilising methanogens (HUM) and acetate-utilising methanogens (AUM) were stable within the 94.0–97.0%, 6.0–3.0%, 1.8–3.6% and 0.6–2.8% ranges, respectively.